2013
DOI: 10.2478/ppb-2013-0022
|View full text |Cite
|
Sign up to set email alerts
|

Test and Math Anxiety: A Validation of the German Test Anxiety Questionnaire

Abstract: The present study investigated the construct validity of the Test Anxiety Questionnaire (Prüfungsangstfragebogen PAF; Hodapp, Rohrmann, & Ringeisen, 2011), a revised and shortened version of the German Test Anxiety Inventory (TAI-G), by comparing it with math anxiety. A sample of German fifth- and sixth-grade students (N = 79; 61 % male) was analyzed. Math anxiety was measured by a German adaptation of the Math Anxiety Questionnaire (Fragebogen für Rechenangst FRA; Krinzinger et al., 2007). A significant b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
26
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 36 publications
8
26
0
Order By: Relevance
“…Again, scores pertaining to the Worry and Lack of Confidence subscales were significantly and negatively correlated with performance motivation, and significant and negative correlations between the PAF subscales and grades were found, particularly math grades. Consistent with these findings, Schnell et al.’s (2013) research on high school students found that the Interference and Lack of Confidence subscale scores were significantly negatively correlated with both math and language performance. Additionally, they found that all of the PAF subscale scores, with the exception of Worry , were significantly positively related to math anxiety.…”
Section: Introductionsupporting
confidence: 52%
See 4 more Smart Citations
“…Again, scores pertaining to the Worry and Lack of Confidence subscales were significantly and negatively correlated with performance motivation, and significant and negative correlations between the PAF subscales and grades were found, particularly math grades. Consistent with these findings, Schnell et al.’s (2013) research on high school students found that the Interference and Lack of Confidence subscale scores were significantly negatively correlated with both math and language performance. Additionally, they found that all of the PAF subscale scores, with the exception of Worry , were significantly positively related to math anxiety.…”
Section: Introductionsupporting
confidence: 52%
“…As for convergent validity, the four subscores associated with the PAF positively correlated with the inhibitory test anxiety measure (Hoferichter et al., 2016), with correlation coefficients of .59, .51, .30, and .18 with Worry , Emotionality , Interference , and Lack of Confidence subscale scores, respectively. Finally, as support for incremental validity, the total score of the PAF was a significant predictor, together with gender, of overall school performance in a regression model that also included gender and math anxiety (Schnell et al., 2013).…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations